E5-((3-phenoxyphenyl)diazenyl)quinolin-8-ol (PPDQ) : A Novel Promising Anticorrosive for Mild Steel in Acid Media, and a Pharmacologically Potent Antidiabetic, Antioxidant Azo Dye - K, Pruthviraj; B. S, Chethan; H., Ramesh; N. K., Lokanath; P. C., Kiran Poral; K. S., Devaraju; N., Narayana Hebbar; K., Sunil (Orbital: The Electronic Journal of Chemistry, 2024)
A novel quinoline based azo dye 5-((3-phenoxyphenyl)diazenyl)quinolin-8-ol (PPDQ) was synthesized using conventional one pot MCR pathway and its structure has been confirmed by multinuclear (1H & 13C) and mass spectral techniques. PPDQ subjected for remarkable analytical applications like anticorrosion potential for mild steel in acidic media. Further, the experimental results were compared with that of the theoretical DFT based calculations and found to be in good agreement with each other. To evaluate the pharmacological activity of the compound invitro antidiabetic and antioxidant activity were carried out. The corrosion inhibition potential of the PPDQ was explored using electrochemical method which exhibited maximum corrosion inhibition efficiency up to 77% on mild steel in 1 M HCl media, further the anticorrosion potential was confirmed by quantum chemical calculations (DFT, ESP diagrams). Antidiabetic activity and antioxidant potency was evaluated using DPPH, and ABTS radical scavenging assay. Further, the in-vitro values were compared with insilico molecular docking studies.